PENGARUH MINUMAN SUPLEMEN TERHADAP KEMAMPUAN LARI 12 MENIT - , Hadwi Prihatanta,Drs; , dr. Suwono., AIFM. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Supplement drinks have been consumed by many athletes for maintaining their practice of physical activities. The best achievement should be supported by high quality food and drink. The aim of this research was to investigate the influence of Hemaviton®, Extra Joss®, Pocari Sweat® energy drink on the ability of physical activities of athletes. This study has observed on 80 students of Sport Science Faculty, Yogyakarta State University (FIK UNY). They were divided randomly into 4 groups, each group consisted of 20 students. In the begining of the study, they performed running for 12 minutes. After taking a rest for 30 minutes and drank Hemaviton Jreng® for first group, Extra Joss® for second group, Pocari Sweat® for third group, and Aqua® for fourth group, they performed 12 minutes run. The distances achieved before and after drinking were measured. Data was measured by meter unit and analysis data use t-pair test, and anava test. The result of this research showed that there are no significance before and after drinking supplement. Also there were no significance different between groups. There is no influence of athlete achievement before and after drinking Hemaviton Extra Joss®, Pocari Sweat®, and Aqua®. The conclusion is that giving supplement energy drinks were able in maintaining the ability of physical activities of the athletes.